Requirements For Applying A Quality Management System in the Sports Field in Light of ISO 9001:2015 (Journal of Hama University, 2024)
The research aimed to determine the requirements for the quality management system in the sports field (karate and bodybuilding federation) in light of the dimensions of the ISO 9001:2015 standard, represented by: the organization context dimension, the leadership dimension, the planning dimension, the support dimension: support, and the operation dimension: activating the available capabilities. after evaluating administrative performance, after continuous improvement of performance.The research relied on the descriptive analytical approach, and the research community included all officials in the karate and bodybuilding federations (the president and members of the two federations, the secretaries, and the senior main committees, in addition to a number of responsible administrators in both federations), so that the total research community in the two federations reached (85). Responsible and administrative, and since the research community was small, a comprehensive inventory method was used, so that the research sample was the research community. Accordingly, the dimensions of the specification were distributed to members of the research sample of (85) officials and administrators, and all distributed questionnaires were obtained with a response rate of (100%).The research found that the requirements for applying the quality management system in accordance with the international standard ISO 9001: 2015 in the karate and bodybuilding federations were accepted by the members of the research sample, and therefore work must be done to provide the application requirements by the management of the two federations in preparation for obtaining the international quality certificate ISO 9001: 2015.
Keywords: Quality Management Sports Field ISO 9001:2015